DETERMINAN MATRIKS ORDO 3X3 DENGAN MENGGUNAKAN METODE CROUT - Vivi Sahira Lestary (PT PUSTAKA CENDEKIA GROUP, 2025)
The determinant is an arrangement of numbers or symbols in the form of a square and presented between twovertical lines. The determinant as a unit that represents a value from the given matrix. The determinant of matrix A is denoted by [A] or det(A). In matrix theory, the calculation of determinants is one of the studies that is often discussed. Calculation of the determinant associated with a small matrix (n ≤ 3) is usually never a problem, only using the definition of the determinant can usually be solved immediately. However, calculating the determinant of a matrix with a large size is difficult to do if you only use the definition of the determinant. Several methods that can be used to calculate the determinant of a matrix are the row reduction method, theLaplace/cofactor expansion method and the Crout method. To determine the determinant of the matrix in this article, the Crout method will be used.